2004
DOI: 10.1590/s0104-42302004000400025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à bacteremia nos portadores de colecistite aguda litiásica

Abstract: Patients with acute calculous cholecystitis have a considerable prevalence of bacteremia in the pre-operative period. It is associated with old age, heart rate, respiratory rate, serum creatinine and systemic inflammatory response syndrome. In patients with acute calculous cholecystitis, presence of bacteremia may be associated to severity of the condition and poor outcome related to pos-operative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…On the other hand, previous studies indicated that positive rates of blood cultures among patients with acute cholangitis ranged from 21 to 71 % [3]. For acute cholecystitis, the prevalence of positive blood cultures is less than acute cholangitis, and in the last two decades it has been reported to range from 7.7 to 15.8 % [28, 31]. Table 2 shows the most recently reported microbial isolates from patients with bacteremic biliary tract infections [14, ].…”
Section: Clinical Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, previous studies indicated that positive rates of blood cultures among patients with acute cholangitis ranged from 21 to 71 % [3]. For acute cholecystitis, the prevalence of positive blood cultures is less than acute cholangitis, and in the last two decades it has been reported to range from 7.7 to 15.8 % [28, 31]. Table 2 shows the most recently reported microbial isolates from patients with bacteremic biliary tract infections [14, ].…”
Section: Clinical Questionsmentioning
confidence: 99%
“…The bacteria commonly found in biliary tract infections are well known, and are presented in Tables 1 and 2 [3,4,[20][21][22][23][24][25][26][27][28][29][30][31]. Antimicrobial therapy largely depends on local antimicrobial susceptibility data.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter study of patients with acute cholangitis showed the proportions of positive blood cultures were 15.2%, 21%, and 25.7% by TG13 severity grade I, II, and III, respectively . For acute cholecystitis, the prevalence of positive blood cultures is less than acute cholangitis, and in the last two decades it has been reported to range from 7.7% to 15.8% . Table demonstrates the most recently reported microbial isolates from patients with bacteremic biliary tract infections .…”
Section: Clinical Questionsmentioning
confidence: 99%
“…The bacteria commonly found in biliary tract infections are well known, and are presented in Tables and . A large‐scale multicenter international observational study was conducted and published in 2017 on epidemiology and microbiology among patients with acute cholangitis .…”
Section: Introductionmentioning
confidence: 99%